An annotated checklist of the Iranian Anthribidae and Nemonychidae (Coleoptera: Curculionoidea) - Ghahari, Hassan; Colonnelli, Enzo (Zootaxa, 2019)
The fauna of Iranian Anthribidae and Nemonychidae (Coleoptera: Curculionoidea) is summarized in this paper. In total, 13 species within nine genera of Anthribidae (Allandrus LeConte, 1876, Enedreytes Schoenherr, 1839, Platyrhinus Clairville, 1798, Platystomos D.H. Schneider, 1791, Dissoleucas Jordan, 1925, Noxius Jordan, 1936, Araecerus Schoenherr, 1823, Choragus Kirby, 1819, and Bruchela Dejean, 1821), and two species of Nemonychidae of the genus Nemonyx L. Redtenbacher, 1845 are listed as occurring in Iran. Two Anthribidae species, Choragus vittatus Reitter, 1885 and Bruchela cretacea K. Daniel & J. Daniel, 1903 are new records for the fauna of Iran.